A Bibliometric Analysis on the state of the art of Neuromarketing research in Web of Science - Ortigueira-Sánchez, Luis Camilo; Risco-Martínez, Santiago Luis (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2022)
Neuromarketing is an ever-evolving field and as such it is important to have an image on where we stand today regarding research about it. In order to study the state of the art of neuromarketing research in Web of Science, we carried out a bibliometric analysis with Vosviewer software. Using the keyword “neuromarketing” as the only search term, we retrieved 184 scientific articles from the Web of Science of Core Collection. We carried out all 5 possible types of analyses allowed on Vosviewer: co-authorship, co-occurrence, citation, bibliographic coupling, and co-citation. The results show that the United States is at the forefront of the field, having the most citations and published documents alongside being the most popular country for co-authored works, and also being the country most involved in citations. Most of the countries heavily involved in neuromarketing research are from Europe, with England being the most involved. Regarding the articles themselves, the most popular keywords are those related to research fields, other than neuromarketing, such as neuroscience, neuroeconomics, advertising, consumer decisions, among others. Likewise, the most popular journals for neuromarketing articles are those in the fields marketing, consumer behavior, psychology, neuroscience, etc. Other results show that the most popular cited journals are from the United States while the most popular cited authors are from Europe.